Air Quality Monitoring System for Smart Cities - Lee, Seng Aik; A Majid, Huda (Progress in Engineering Application and Technology, 2022)
Nitrogen, oxygen, carbon monoxide, and traces of several rare elements are all found in air. Humans require a contaminant-free environment in which to live. This is extremely important for human survival and health. Any change in the natural composition of air could endanger life on the planet. We can control any electrical equipment in homes and businesses using the Internet of Things (IOT). Users can read data from any sensor and analyze it graphically from anywhere in the world with this project. Using Arduino Uno and LoRa, we can read the air quality data from the MQ135 air quality sensor and upload it to a ThingSpeak cloud.